Peningkatan Produktivitas Pengusaha Tempe - Tri Kurniawati; Naili Sa’ida; Wahono Wahono; Panji Hermoyo (Universitas Muhammadiyah Surabaya, 2018)
The economic crisis hit the world which had a direct impact to worsen economic conditions in Indonesia. Economic conditions from 1997 to 1998, only MSMEs were able to survive. One form of MSMEs in rural areas is tempe business. Tempe is one of the original foods from Indonesia, which comes from fermented soybeans. Tempe is a daily food consumed by almost all Indonesian people. Tempe is a food that is consumed almost every day by people in the Pilangkenceng sub-district. Most are consumed as side dishes and are also used as souvenirs (tempe chips). Community service activities include holding meetings, conducting FGDs, handing over tools and monitoring. The results of this assistance include 2 aspects, namely management aspects and production aspects. Conclusion The Community Partnership Program needs to be done as the role of lecturers to improve the community Community Partnership Program is able to increase the amount of production and competitiveness of Partners.